More, and More Productive, Jobs for Nigeria : A Profile of Work and Workers - World Bank (World Bank, Washington, DC, 2016)
This report provides an overview of jobs,workers, and employment opportunities in Nigeria, using recent household data. Jobs are critical for Nigeria’s present and future, as better jobs and income-earning opportunities form the basis for more diversified economic growth, poverty reduction, and greater prosperity. This report relies heavily on the wealth of information gathered through the General Household Survey conducted by the National Bureau of Statistics. The diagnostics included in this report are intended to describe the landscape of jobs in the country and provide broad analysis as an input into the development of a jobs strategy for Nigeria. The analysis conducted for this report has highlighted three areas that need attention: (i) data quality issues, as shown in the several rounds of data cleaning needed to provide consistent statistics; (ii) poor documentation and archiving, which prevented the use of several rounds of the household survey, especially to produce national-level statistics using population weights; and (iii) standardization, to permit comparisons of key variables over time and track the impact of policy changes and other events. As shown in this report, many Nigerians work, but generally in low-earning activities. Most work opportunities in the country are informal and do not come with a wage. This report presents an updated picture of jobs in Nigeria and identifies opportunities for improving the quality of jobs. This report has shown that Nigeria combines middle-income status and Africa’s largest economic power with high poverty levels, largely because the main sectors of economic growth are disconnected from the sectors that provide employment, notably subsistence activities in the agricultural and services sectors. Finally, the diagnostics included in this report show that both new and existing jobs, whether in agriculture or other sectors, will need to be more productive to help the population move out of low-earning employment and poverty.